PSIX-2 Effects of early heat conditioning on heat stress-induced changes in broiler growth performance, oxidative stress in blood, and quality parameters in breast meat. (7th December 2018) - Punchihewage Don, A; Attuquayefio, W; Oh, S; Feng, X; Ahn, D; Min, B
Abstract: Environmental temperature has increased due to climate change, which affected broiler productivity and meat quality. Early heat conditioning (EHC) is a technique utilizing chick's perinatal epigenetic temperature adaptation ability to improve heat tolerance of broilers. This study was aimed to determine mitigating effects of EHC against chronic (C-HS) and acute heat stress (A-HS) during the finishing period on growth performance, oxidative stress in blood and breast meat quality of broilers. One hundred eighty 1-day-old Cobb broiler chicks in 30 pens were randomly allotted to 5 groups and raised for 42 days; Two groups at 3d were exposed to EHC at 36 °C for 12h, then subjected to C-HS (12h-cyclic temperature control at 34/27 °C for the last one week) and A-HS (at 36 °C for 2h at Day 41), respectively. Two no-EHC groups were exposed to both heat challenges as negative controls, respectively. Control were without EHC and HS. Growth performance, plasma oxidative stress markers, and quality parameters of breast meat harvested at Day 43 were determined. Data were analyzed using proc mixed or glm and least-square means were compared using PDIFF. The effects of both HS against growth performance were significant but mitigated by EHC (p<0.05). C-HS more severely affected weight gain and feed conversion ratio than A-HS due to its duration (p<0.05). EHC and/or HS did not affect plasma oxidative stress markers. Protein oxidation and antioxidant capacity in meat was significantly affected by HS, more severely by A-HC, compared to Control, and EHC alleviated their effects (p<0.05). Other meat quality parameters were not affected by EHC and/or HS. The results suggested that EHC can minimize HS effects against broiler growth performance and oxidative stability of breast meat. More Severe HS could further increase oxidative susceptibility in meat to the level causing quality defects, and EHC could reduce them.